Investigation into sustainable technologies for mitigating urban heat island effects in subtropical monsoon climate - Zheng, Tianhong (2023)
The urban heat island (UHI) is a concerning environmental phenomenon, and mitigation strategies have been proposed to reduce its adverse effects. This study conducted a literature review of UHI and UHI mitigation strategies, finding that urban cooling technologies such as green roofs, cool roofs, and urban vegetation can comprehensively affect meteorological parameters (temperature, sky view factor, radiation, etc.), urban building energy use, carbon emissions and improve human comfort. Additionally, thermal energy storage technologies were also reviewed, with a focus on mitigating UHI. The study assessed the effectiveness of conventional and thermal energy storage-based UHI mitigation strategies through meteorological simulations using the software ENVI-met and a novel model called UHIMS-ECHE. The simulation results showed that conventional UHI mitigation scenarios can reduce UHI intensity, building cooling energy use, carbon emissions, and improve human thermal comfort. Moreover, the integration of phase change materials (PCMs) and photovoltaic (PV) systems was analysed by the UHIMS-ECHE model, which demonstrated that the integration of PCM and PV technologies can significantly reduce UHI, improve energy efficiency, and enhance human thermal comfort in urban environments. A case study has been conducted in Osaka, Japan, which is a typical city under subtropical monsoon weather condition. Consequently, the PCM-Roof -A36H -10cm model reduced outdoor air temperatures by up to 7.09°C and total urban building cooling energy use cooling loads by up to 23.68% compared to the baseline case. These findings provide insights for policymakers, urban planners, and building designers to create sustainable urban environments. Further research is recommended to investigate the feasibility and cost-effectiveness of these technologies in different urban contexts and climatic conditions.